Plasma Procalcitonin Is Useful for Predicting the Severity of Acute Cholecystitis - Saben Sakalar; Engin Ozakın; Arif Alper Cevik; Nurdan Acar; Serkan Dogan; Filiz Baloglu Kaya; Taylan Kara (Emergency Medicine International)
Background. Acute cholecystitis is a common complication of cholelithiasis. Delayed diagnosis may constitute morbidity and mortality; therefore, early diagnosis and determining the severity of acute cholecystitis are crucial. Objectives. This study aimed to determine the validity of blood procalcitonin (PCT) levels in assessing the severity of acute cholecystitis. Methods. The Emergency Department (ED) patients diagnosed as acute cholecystitis were included in the study. Patients were allocated into three severity grades according to the Tokyo Guidelines 2013. PCT level was measured after the clinical and radiological diagnosis of acute cholecystitis in the ED. Results. Ninety-five patients diagnosed with acute cholecystitis, among them 48 of were male. Forty patients (42.1%) were allocated to grade 1, 19 (20%) to grade 2, and 36 (37.9%) to grade 3. The median values of PCT were 0.104 ng/ml, 0.353 ng/ml, and 1.466 ng/ml for grade 1, 2, and 3 patients, respectively (p<0.001). Conclusion. Blood procalcitonin levels can be used to determine the severity of acute cholecystitis effectively.